Quality of life and working context of nursing professionals of the Family Health Strategy - Ana Luísa Nunes Marques; Maria Beatriz Guimarães Ferreira; Joyce Mara Gabriel Duarte; Nara dos Santos Costa; Vanderlei José Haas; Ana Lúcia de Assis Simões (Rev Rene)
Objective: to examine the relationship between working context and quality of life of nursing professionals of the FamilyHealth Strategy. Methods: observational, cross-sectional study with quantitative approach accomplished with 50 nursingprofessionals from urban and rural areas. Participants answered a questionnaire of socio-demographic and professionalcharacterization, the Work Context Assessment Scale and WHOQOL-brief. Data were submitted to exploratory and bivariateanalysis. Results: predominance of women, married, belonging to economic classes C/D and with only one employmentbond. The factor Work Organization and the Social domain had higher mean scores, while Socio-professional relations andthe Environmental domain, lower scores. Descriptively, there was a negative correlation between all the factors of the workcontext and the Physical, Psychological and Social domains. Conclusion: inadequate conditions to work practice, lack oforganization and the difficulty in social relationships negatively impact the quality of life of nursing professionals.